(untitled) (Conferencea, 2024)
The article presents the psychological conditions for the development of a culture of tolerance in biology in its teachers. Excessive inclusion of stereotypes in professional activities has been recognized as one of the causes of professional change. With work experience, stereotyped approaches are established, simplifying assessment, the list of ready-made solutions is absolved.